The Influence of Principal Leadership and Work Discipline on Teacher Performance at SD Negeri 2 Angsau - Sulasih; Sunoto, Hadi (Cattleya Darmaya Fortuna, 2023)
This research aims to: 1) Identify whether the school principal's leadership influences teachers' performance or not; 2) Determine whether teachers' work discipline has an impact on their performance or not; 3) Investigate whether the school principal's leadership and teachers' work discipline together influence teachers' performance. The research subject is SDN 2 Angsau Pelaihari. This research employs a quantitative method with a total of 34 respondents.. The results indicate that: 1) There is a very significant positive influence between the school principal's leadership style and teachers' performance; 2) There is a very significant positive influence between job satisfaction and teachers' performance; 3) There is a positive influence between organizational commitment and job satisfaction together on teachers' performance on 81.8%.